Geographic information system for marine ecotourism and rural lifestyle in Prachuap Khiri Khan - Puengsom, Sompond; Polpong, Jakkapong; Pornpongtechavanich, Phisit (Institute of Advanced Engineering and Science, 2025)
According to the Prachuap Khiri Khan Province tourism statistics report for 2023, there were 11,143,079 Thai and foreign tourists from January to December 2023, which increased by 1,395,195 people or 14.31 percent compared to 2022. Simultaneously, tourist attractions accumulated tourism income in 2023 totaling 44,241 million baht, marking an increase of 11,402.63 million baht or 34.72 percent from 2022. Despite this growth, tourist attractions that are popular with tourists remain centered in Hua Hin District due to a lack of publicity and insufficient information provided to tourists. Consequently, the researcher intended to develop a geographic information system (GIS) for marine ecotourism and rural lifestyles in Prachuap Khiri Khan Province to promote rural tourist attractions and distribute tourism income to the community. The system utilized the classification (precision and recall) model and was developed using ArcGIS and the web app builder ArcGIS. Findings from 8 experts in computers, information technology (IT), and GIS indicated that the overall system efficiency had an average of 4.54 and a standard deviation of 0.50. Additionally, results from the study on retrieval efficiency using the classification (precision and recall) model revealed a precision value of 0.90 and a recall value of 0.95.